Penyuluhan dan pelatihan jurnalistik & E-preneurship di pondok pesantren Madinatul quran cilodong - Sukma, Agus Hitopa; Permana, Dwi Sidik (Jurnal Pengabdian Teratai, 2020)
The topic of this activities chosen was "journalism & e-preneurship counseling and training at Madinatul Quran Islamic Boarding School in Cilodong". The main objective are: the adaptive character of students embedding to face all changes in business in the 4.0 era, build the ability to pioneer digital-based independent businesses (e-preneurship) and brief the journalism and online creativity opportunities for students. The method used by the implementation team are counseling in group learning, as conventional teaching and problem solving model. The method did not appliy the assessment system. The recruitment pattern is fully the authority of the Director of Education in Islamic Boarding Schools which is decided based on the considerations of the religious teachers and is known by the foundation. With this counseling activity, they were more aware of their positioning in which will actually be able to play a wider role in the community. However the progress of civilization, then the turning point of humans will be directed to religion, the need for trust which is the capital in the business. Being the tahfidz will place them as high social trust. It is very strategic to start a business.